Intelligence and Autonomy - Ted Krueger (Oz, 2001)
The terms “Intelligent Buildings” and “Smart Buildings” have been used in the building industry for almost two decades. They refer to a wide variety of capabilities integrated into the building fabric based on computer and communications technologies.